Preparation and characterization of scaffold nanofibers by electrospinning, based on chitosan and fibroin from Silkworm (Bombyx mori) (2017)
(Eng) Here we present a study on the preparation of scaffolding for nanofibers composed of chitosan (QS) and fibroin from cocoon silkworm (Bombyx mori) (FGS) for its potential use in biomedicine. The scaffolds conformed by nanofibers were prepared from different mixtures of QS and FGS. They were characterized with analytical techniques such as scanning electron microscopy-SEM, infrared spectroscopy-FTIR, X-ray diffraction-XRD, Thermogravimetric Analysis-TGA, Differential Scanning Calorimetry-DSC and Citocompatibility tests, to determine its morphology, functional groups, thermal transitions, and cell viability of the scaffolding QS/FGS. Nanofibers of different diameters of QS/FGS (8-177 nm) were obtained and compared with the fibers of cocoons (22-36 μm) and fibroin (7-13 μm). The best scaffolds were achieved from a physical mixture with a weight ratio QS: FGS (1:3) dissolved in trifluoroacetic acid under the following electrospinning parameters. Voltage: 20 kV, injection flow: 0.5 ml/h, needle-collector distance: 12 cm, relative humidity: 28% Temperature: 25 ° C. It was determined that the scaffolding QS/FGS possessed fibers with nanometric diameters less than 200 nm, which allow optimal cell adhesion and thermal stability at the application site, with a view to control the degradation of the scaffold. Thermal analyses, supplemented with XRD studies reveal the internal structure of the fibers. Besides Cytocompatibility test on prepared cell scaffolds, it indicates that the integrity requirement was achieved and the necessity to control the pH to achieve an increased cell viability. The results show that nanofibers QS/FGS can be a good candidate for tissue engineering in biomedical applications such as scaffolds.